Comparing pharmacological and bioelectronic approaches for the treatment of gastrointestinal disorders. Issue 4 (9th April 2019) - Furness, John
Professor John Furness speaks to Alice Bough, Commissioning Editor. Professor John Furness leads the Digestive Physiology and Nutrition Laboratory at the Florey Institute of Neuroscience and Mental Health and the University of Melbourne, where he has appointments in the Medical and Veterinary and Agricultural Sciences Faculties. His laboratory has worked for many years on the physiology of digestion, particularly its neuronal and endocrine control. A current emphasis of his work is on the relationships between diet, environment and gut health, and their implications for animal production and for human wellbeing. He is also investigating therapies for the treatment of inflammatory bowel disease and the roles of gut hormones. He has worked closely with the pharmaceutical, medical devices and animal production industries. He is one of the most highly cited Australian scientists. Google Scholar (January 2019) gives his h-index as 107, including 40, 400 citations overall.